Активное термостатирование полупроводниковых СВЧ-генераторов - Kravchenko, A. V.; Plaksin, S. V.; Sokolovskiy, I. I. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
The problem of temperature stabilization of semiconductor generator parameters is considered. A reversible continuous thermal control circuit with unipolar power supply based on thermoelectric microcoolers utilizing the Peltier effect is presented. A temperature coefficient of frequency not worse than 10–7 1/°C has been achieved in the temperature range of +60…–70 °C for waveguide generators on Gunn diodes in the frequency range of 32–37 GHz.